Constructing ample active sites in nitrogen-doped carbon materials for efficient electrocatalytic carbon dioxide reduction. (December 2021) - Wang, Xingpu; Li, Xueyan; Ding, Shaosong; Chen, Yalan; Liu, You; Fang, Mingwei; Xiao, Guozheng; Zhu, Ying
Abstract: Seeking catalysts with high density of active sites of N-doped carbon nanomaterials is desired for effective conversion of CO2 to CO. Here, the density functional theory (DFT) calculation is employed to investigate the formation energy and chemical potential of N species from different N-containing carbon precursors. It is found that the hybrid precursors facilitate to form high density of the pyridinic-N active sites, owing to its lower formation energy of pyridinic-N. Accordingly, we develop a hybridization strategy of precursors to fabricate the N-doped porous carbon (NPC) with a pyridinic-N content of 2.86 wt% by ball milling of the poly(aniline-co-pyrrole) copolymer in the presence salt templets, followed by pyrolysis. As expected, the optimized NPC1: 0.5 exhibits an excellent activity toward CO2 RR with the CO Faradaic efficiency of ∼95.3% and a high CO current density of 4.3 mA cm −2, higher than most of the previous reports. Besides, this NPC had CO current density of 115.9 mA cm −2 and a long-term stability for 20 h in flow cell. The experiments and DFT calculation show that the pyridinic-N species act as active sites for CO2 RR. In addition, 2p electrons of pyridinic-N species promote *COOH intermediate release to enhance CO2 conversion toward CO. Graphical Abstract: We developed a hybridization strategy of precursors to fabricate the N-doped porous carbon with high density pyridinic-N content by ball milling of the poly(aniline-co-pyrrole) copolymer in the presence salt templets, followed by pyrolysis. The as-prepared catalyst exhibits an excellent electrocatalytic activity for CO2 to CO. DFT calculations reveal that 2p electrons of pyridinic-N species promote *COOH intermediate release to enhance CO2 conversion toward CO. ga1 Highlights: The hybrid N resource contributes to form N-doped carbon with ample pyridinic-N. NPC1:0.5 exhibits an excellent FECO of 95.3% with a high JCO of 4.3 mA cm −2 . The 2p electrons provide a facility for releasing *COOH to enhance CO2 conversion.